2021
DOI: 10.1007/s00405-020-06567-7
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal sodium citrate in quantitative and qualitative olfactory dysfunction: results from a prospective, controlled trial of prolonged use in 60 patients

Abstract: Objectives We have previously shown that treatment with intranasal sodium citrate may be beneficial in post-infectious olfactory dysfunction. Sodium citrate reduces free intranasal calcium and is, therefore, thought to prevent calcium-mediated feedback inhibition at the level of the olfactory receptor. We aimed to determine whether treatment with a 2-week course of intranasal sodium citrate improves quantitative olfactory function in patients with post-infectious impairment. We also aimed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
0
23
0
4
Order By: Relevance
“…In a prospective observational study, the duration of effect subjectively reported by patients was 3 hours. 1807 The subsequent study by Whitcroft et al 1806 that looked specifically at PIOD showed an effect on combined threshold and identification scores, but not separately. 1806 The method of application differed among the four studies.…”
mentioning
confidence: 98%
“…In a prospective observational study, the duration of effect subjectively reported by patients was 3 hours. 1807 The subsequent study by Whitcroft et al 1806 that looked specifically at PIOD showed an effect on combined threshold and identification scores, but not separately. 1806 The method of application differed among the four studies.…”
mentioning
confidence: 98%
“…Intranasal treatments such as topical corticosteroids have been trialled in olfactory loss and subsequently applied to parosmia, although there is little evidence to support this. A small trial of intranasal sodium citrate reported improvements in phantosmia but not parosmia or hyposmia,12 and the results may simply reflect the natural course of the symptoms rather than the effectiveness of treatment. Evidence for other treatments is lacking, although trials are ongoing.…”
Section: What Practical Advice Can Be Offered?mentioning
confidence: 99%
“…Numerous drugs exert potential therapeutic effects on OD: vitamin A, theophylline, intranasal sodium citrate, caroverine, alpha-lipoic acid, minocycline, zinc sulfate, and ginkgo biloba ( 112 , 113 , 132 , 133 ). However, except for one case report on vitamin A, clinical studies on their efficacy in COVID-19-induced OD are lacking, so most of these drugs are not recommended for routine use ( 134 ).…”
Section: Mechanisms Of Covid-19-induced Odmentioning
confidence: 99%